An Assessment of Publication Status of Pediatric Liver Transplantation Studies. - Thomas Breil; Daniel Wenning; Ulrike Teufel; Georg F Hoffmann; Markus Ries (PLoS ONE, 2016)
Pediatric liver transplantation is a highly specialized, challenging field. Selective reporting may introduce bias into evidence based clinical decision making, but the precise extent of unpublished data in pediatric liver transplantation is unknown today. We therefore assessed the public availability of completed clinical trials in pediatric liver transplantation.We determined the proportion of published and unpublished pre-registered, completed pediatric liver transplantation studies on ClinicalTrials.gov. The major trial and literature databases, i.e., clinicaltrials.gov, Pubmed, and Google Scholar were searched for publications. In addition, principal investigators or sponsors were contacted directly. STROBE criteria were applied for the descriptive analysis.Out of N = 33 studies focusing on pediatric liver transplantation registered as completed until March 2014 on clinicaltrials.gov, N = 19 (58%) studies were published until February 2015, whereas N = 14 (42%) studies remained unpublished. The unpublished trials contain data from N = 2105 (35%) patients out of a total population of N = 6044 study participants. Median time-to-publication, i.e., the period from completion of the trial until public availability of the data was 23 IQR 10 to 28 months. Most pertinent key questions in pediatric liver transplantation, i.e., surgical procedures, immunosuppression, concomitant infections, and graft rejection were addressed in 48% of studies (N = 16/33), half of which were published.Half of the clinical trials in pediatric liver transplantation focused on key questions such as surgical procedures, immunosuppression, concomitant infections, and graft rejection. There is still a considerable amount of unpublished studies results in pediatric liver transplantation. Time from study completion to publication was almost twice as long as the 12 months mandatory FDAAA-timeline with a trend towards acceleration over time. The data should serve as a baseline for future progress in the field. More stringent publication of completed trials and focused multicenter research should be encouraged.